Association between mean platelet volume and severity of disease in patients with obstructive sleep apnea syndrome without risk factors for cardiovascular disease - Mustafa Serkan Karakaş; Refik Emre Altekin; Ahmet Oğuz Baktır; Murathan Küçük; Aykut Çilli; Selim Yalçınkaya (Türk Kardiyoloji Derneği Arşivi, 2013)
Objectives: Obstructive sleep apnea syndrome (OSAS) is associated with increased cardiovascular morbidity and mortality. Platelet activation and aggregation are central processes in the pathophysiology of atherothrombosis. Mean platelet volume (MPV), a determinant of platelet activation, is a newly-emerging risk factor for atherothrombosis. Therefore, we have investigated the possible association between OSAS and MPV. Study design: We selected 30 mild, 32 moderate, and 31 severe OSAS patients and 31 healthy control subjects matched for age, sex, and body mass index. MPV was measured using an automated blood cell counter. Results: The MPV levels were significantly higher in the severe OSA group than in the control group (8.6+-1.1 vs. 7.8+-0.7 fl, p=0.03). There were no significant differences in respect to MPV between controls and patients with mild and moderate OSA (7.8+-0.7 vs. 8.3+-1.2 fl, p=0.2; 7.8+-0.7 vs. 8.4+-1.3 fl, p=0.08) and between patients with mild, moderate, and severe OSA (8.3+-1.2 vs. 8.4+-1.3 vs. 8.6+-1.1 fl, p=0.9). Significant correlations were seen between MPV and apneahypopnea index (r=0.347, p≤0.001), minimal oxygen saturation (r=-0.224, p=0.03), and the percentage of recording time spent at a oxygen saturation less than 90% (r=0.240, p=0.02). Conclusion: Our results suggest that OSAS patients tend to have relatively increased platelet activation andatherothrombotic risk.